2016
DOI: 10.1016/j.theriogenology.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular transfer of fresh and vitrified immature bovine oocytes

Abstract: Embryo production by intrafollicular oocyte transfer (IFOT) represents an alternative for production of a large number of embryos without requiring any hormones and only basic laboratory handling. We aimed to (1) evaluate the efficiency of IFOT using immature oocytes (IFIOT) and (2) compare embryo development after IFIOT using fresh or vitrified immature oocytes. First, six IFIOTs were performed using immature oocytes obtained by ovum pickup. After insemination and uterine flush for embryo recovery, 21.3% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
1
23
1
7
Order By: Relevance
“…In that study, in vivo oocyte maturation rates after injecting 3 to 9 cumulus oocyte complexes (COCs) into preovulatory (30-36 mm) follicles were similar to in vitro maturation. Recently, we and others (Kassens et al, 2015;Spricigo et al, 2016) have tested the feasibility of injecting COCs into dominant follicles and confirmed that this technology can also be applied in cattle. This model in cattle still needs further validation to ensure that one preovulatory follicle is able to maintain injected-oocytes viability.…”
Section: Oocyte and Meiotic Resumptionsupporting
confidence: 60%
See 1 more Smart Citation
“…In that study, in vivo oocyte maturation rates after injecting 3 to 9 cumulus oocyte complexes (COCs) into preovulatory (30-36 mm) follicles were similar to in vitro maturation. Recently, we and others (Kassens et al, 2015;Spricigo et al, 2016) have tested the feasibility of injecting COCs into dominant follicles and confirmed that this technology can also be applied in cattle. This model in cattle still needs further validation to ensure that one preovulatory follicle is able to maintain injected-oocytes viability.…”
Section: Oocyte and Meiotic Resumptionsupporting
confidence: 60%
“…This model in cattle still needs further validation to ensure that one preovulatory follicle is able to maintain injected-oocytes viability. Recovery rates and embryo development rates need to be improved to allow the adoption of intrafollicular oocyte transfer (IFOT) under field conditions (Spricigo et al, 2016).…”
Section: Oocyte and Meiotic Resumptionmentioning
confidence: 99%
“…This study demonstrated that even in vitro maturation can be bypassed by direct transfer of collection cumulus-oocytes complexes into the follicle (Hoelker et al 2017). Intrafollicular oocyte transfer using immature fresh or vitrified oocytes collected from living donors using transvaginal aspiration was reported (Sprícigo et al 2016). Although IFOT did not improve the developmental competence of vitrified oocytes, viable blastocysts and pregnancies were achieved after transfer of fresh immature oocytes.…”
mentioning
confidence: 84%
“…However, the reported techniques did not support field applications. In the same way, the intra-follicular transfer of oocytes showed interesting results, but requires specialist skill to transfer oocytes into the follicular antrum (SPRÍCIGO et al, 2016). Thus, our group has proven the feasibility of nonsurgical embryo transfer techniques in small ruminants (FONSECA et al, 2014) and, in this study, we used this new technique to perform the maturation of bovine oocytes in a goat's uterus, whilst aiming to establish an efficient and practical method of ex situ maturation for bovine oocytes.…”
Section: Introductionmentioning
confidence: 94%